Reconstructing Obesity : The Meaning of Measures and the Measure of Meanings - Jessica A. Hardin, Megan B. McCullough (Berghahn Books, 2013)
â€œThat is child abuse!â€ one my Anthropology of the Body students declared, ruffl ed and aff ronted, after learning about gavage, the forced feeding and fattening of young Muslim girls in certain West African subcultures (Popenoe 2005). When thinking about fat, college students articulate very clear ideas about what constitutes a â€œhealthyâ€ body, and their responses to fatness and obesity, words often used interchangeably, range from baffl ed, outraged, curious, to liberated as they are asked to unpack their ideas about fat, value, and health. When my classes have analytically examined fat and obesity, individually and collectively, students learned to identify tendrils of culturally located morality discourses woven into concepts and beliefs about fatness, including the belief in the United States that all fat equaled ill health. Students struggled to identify and grasp the way fat is culturally gendered and that fat, such as that discussed above regarding gavage, is hard to imagine as something of beauty or value. Similarly in teaching â€œTh e Sweetness of Fatâ€ by Sobo (1994), Jessica found that students could only explain Jamaican concepts of health, nurturance, and moral worth embodied in fatness when it was a creation of a precarious economic and agricultural environment. For Jessicaâ€™s undergraduate students, fatness could only be valued and thinness avoided in an environment of scarcity, thus they constructed a linear and evolutionary perspective in which fatness decreases in value as development and knowledge increases, thereby placing Euro-American cultural understandings of fatness at the top of their progression.